The impact of international service on the development of volunteers’ intercultural relations - Lough, Benjamin J.; Sherraden, Margaret Sherrard; McBride, Amanda Moore; Xiang, Xiaoling (Social science research, 2014)
•A quasi-experimental longitudinal design assesses impacts on international volunteers.•Volunteers report significant increases in international and intercultural constructs.•A comparison group did not report similar increases across all categories. Approximately one million people from the United States perform international volunteer service each year, representing a significant flow of ideas, people, resources, and aid across international borders. This quasi-experimental study assesses the longitudinal impact of international volunteer service on volunteers’ intercultural relations, international social capital, and concern about international affairs. Using linear mixed regression models that control for a counterfactual comparison group of individuals that did not travel abroad, international volunteers are more likely to report significant increases in international social capital and international concern two to three years after returning from service. Results indicate that intercultural relations may also continue to increase years after returning from service. International service may be a useful approach to helping people gain skills and networks that are needed in an increasingly global society.